Description of a traffic bridge of the Cantabrian SpeedWay made of composite materials - J. M. Mieres; I. Calvo; A. Miravete; E. Gutiérrez; E. Shahidi; C. López; J. Cuartero; P. Comino; R. Guzmán de Villoria (Materiales de Construccion, 2006)
In july 2004 a 46 metres length bridge was placed at the Cantábrico Highway between Tamón (Carreño) - Otur (Luarca) that place is located near Asturias airport. This particular bridge has been manufactured mainly with composite materials. This bridge is the final result of an Iberoeka “Pumacom” funded project launched at the beginning of 2003. An innovative issue was the beams of the structure totally manufactured with epoxy/carbon fibre laminated on polyurethane preforms. Another very interesting challenge considered in this project is the joint between longitudinal bridge beams and the supporting platform made of light mortar and steel rods. Joints and connectors were made of AR galls fiber pultruded profiles.